Determination of total phenolic content, antioxidant and monophenolase inhibition activities of Carica papaya peel extracts in solvents with different polarity/ Nur Izzati Athirah Zakaria and Salfarina Ramli - Zakaria, Nur Izzati Athirah; Ramli, Salfarina (Faculty of Pharmacy, 2020)
Dysregulation of melanin production that is catalyzed by an enzyme known as tyrosinase may lead to skin hyperpigmentation. Even though fruit peels are often regarded as waste product, they can be a good source of phytochemicals with potent biological activities that can be utilized to inhibit tyrosinase and reduce hyperpigmentation. This study was carried out to determine the phenolic content, antioxidant and monophenolase inhibition activities of Carica papaya (C. papaya) peel extracts prepared using three solvents with different polarity; ethanol, ethyl acetate and petroleum ether. The total phenolic content was determined according to Folin-Ciocalteu method while the antioxidant and monophenolase inhibition activities of the plant extracts were evaluated using 2,2-diphenyl-1-picrylhydrazyl (DPPH) and tyrosinase inhibitory assays respectively. There was no significant difference in total phenolic content and antioxidant activities of the extracts (p > 0.05). However, the ethanolic extract of C. papaya peel showed the highest phenolic content (0.58 ± 0.19 mg/g) and maximum antioxidant activity (IC50 = 164.27 μg/mL) compared to ethyl acetate and petroleum ether. There was a significance difference in monophenolase inhibition activities of the extracts (p < 0.05). Ethyl acetate extract exhibited excellent monophenolase inhibition activity (82.69 ± 2.57 %) compared to other solvents. Finding of this study can be used for future researches to study the biological activities and elucidate the chemical structure of active compounds involved.